Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd006313.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous versus inhalation anaesthesia for one-lung ventilation

Abstract: There is no evidence from randomized controlled trials of differences in patient outcomes for anaesthesia maintained by intravenous versus inhalational anaesthesia during one-lung ventilation. This review highlights the need for continued research into the use of intravenous versus inhalation anaesthesia for one-lung ventilation. Future trials should have standardized outcome measures such as death, adverse postoperative outcomes and intraoperative awareness. Dropouts and losses to follow up should be reported. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…They found no evidence regarding the effect of maintenance anesthetic agents on participants’ outcomes (11). In addition, in another similar systematic review done by Bassi et al (12), the same results were obtained. These results were in agreement with our results concerning the similar pressure of arterial oxygen, patients` blood pressure and heart rate in both groups.…”
Section: Discussionsupporting
confidence: 76%
“…They found no evidence regarding the effect of maintenance anesthetic agents on participants’ outcomes (11). In addition, in another similar systematic review done by Bassi et al (12), the same results were obtained. These results were in agreement with our results concerning the similar pressure of arterial oxygen, patients` blood pressure and heart rate in both groups.…”
Section: Discussionsupporting
confidence: 76%
“…The language is also limited to English, which may increase the risk of publication bias. Therefore, if researchers doubt the prognostic value of different anesthetics during OLV, as recommended by two Cochrane meta-analyses [ 3 , 7 ], then higher quality, more extensive trials should be designed and conducted in the future to evaluate expected outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Christopher, et al found that in cardiac surgery, inhalation anesthesia was associated with a significant outcome advantage and lower mortality [6]. However, Bassi, A [7] and Modolo, NS [3] found little evidence from randomized controlled trials (RCTs) in 2008 and 2013 that showed significant differences in specific postoperative outcomes between general anesthesia maintained with inhalation and intravenous anesthesia such as propofol in the case of OLV. Subsequently, several RCTs and systematic reviews have suggested that inhaled anesthesia may preserve cardiac function, decrease PPC, and attenuate local alveolar inflammatory responses in patients undergoing OLV [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Although work published in the 1980s was able to make a clear association between the blunting of hypoxic pulmonary vasoconstriction (HPV) and inhalational anesthetics in rat lungs [20], a recent meta-analysis by Bassi et al [21 ] was unable to demonstrate a benefit of one technique over the other in humans. A study published by De Conno et al [22 ] showed that patients receiving the volatile anesthetic sevoflurane during OLV expressed lower levels of inflammatory mediators than patients receiving a target controlled infusion of propofol.…”
Section: Anesthetic Implicationsmentioning
confidence: 99%